Crystal structure of 2-(6-methoxynaphthalen-2-yl)-N-(4-morpholinophenyl)propanamide, C24H26N2O3 - Zhang Qing; Xue De-Dong; Han Li-Wei (Zeitschrift für Kristallographie - New Crystal Structures)
C24H26N2O3, monoclinic, P21/n (no. 14), a = 6.565(3) Å, b = 36.126(13) Å, c = 8.423(3) Å, β = 97.745(15)°, V = 1979.4(14) Å3, Z = 4, Rgt (F) = 0.0329, wRref (F 2) = 0.0884, T = 100(2) K.